a basic math for pensum of the DAC Administration and Academic careers (Revista Electrónica REDINE, 2018)
This study, we present the results of an investigation under mode feasible project, whose aim was to propose the inclusion of mathematics in the curriculum of studies of the careers of Business Administration and Public Accounting offered Lisandro Alvarado University of Barquisimeto Edo. Lara. During the needs analysis, a diagnosis was made to the world of new students during the first quarter of 2004. The results showed little domain knowledge and mathematical difficulties in the application of logical reasoning in solving problems. These results demonstrate the need to present the new students of the DAC, to be liveled through a Basic Mathematics.
Keywords: basic mathematics; diagnosis; mastery of basic mathematical skills; leveling of the basics of mathematics